2018
DOI: 10.1002/mp.13142
|View full text |Cite
|
Sign up to set email alerts
|

Early diabetic retinopathy diagnosis based on local retinal blood vessel analysis in optical coherence tomography angiography (OCTA) images

Abstract: We developed a new DR-CAD system that is capable of diagnosing DR in its early stage. The proposed system is based on extracting three different features from the segmented OCTA images, which reflect the changes in the retinal vasculature network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…We plan to use greater levels of information from these OCT-As such as by using deep or intermediate capillary plexi. Previous articles 8 suggest that level of information can be improved by accessing these deep capillary plexi, and we also plan to use new imaging scanners presenting larger areas for analysis. Additional patient metadata such as recent specific symptoms and details of race and sex might further increase the power of the classification algorithms and provide more assurance on external validity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We plan to use greater levels of information from these OCT-As such as by using deep or intermediate capillary plexi. Previous articles 8 suggest that level of information can be improved by accessing these deep capillary plexi, and we also plan to use new imaging scanners presenting larger areas for analysis. Additional patient metadata such as recent specific symptoms and details of race and sex might further increase the power of the classification algorithms and provide more assurance on external validity.…”
Section: Discussionmentioning
confidence: 99%
“…They found that superficial plexus vessel density had the highest area under the receiver operating characteristic (ROC) curve (area under curve [AUC]) of 0.893, compared with features such as foveal avascular zone (FAZ) area (0.472) and vessel density in the deep plexus (0.703). More recent studies by Eladawi et al 8 have progressed to demonstrate the ability to distinguish normal patients from those who were diabetic with retinopathy (DR) by combining OCT-A features using a machine learning algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies use their own quantification algorithm, where the vessel detections vary from using global thresholding [11], binarization and skeletonization [12], to more complex filtering and thresholding approaches [3,14]. More advanced methods include local fractal dimension [9], and a probabilistic model utilizing the 3D spatial information from both the superficial and the deep layer [8]. Some OCTA devices provide proprietary software for extracting vessel densities, e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Larger vessels are defined as vessels of twice (or more) the radius of the capillaries. Similarly to the study by Eladawi et al [8], manual annotations are produced and used as ground truth (GT). Two images acquired as described in section 3.1 were annotated manually by AMEE.…”
Section: Dictionary-based Segmentationmentioning
confidence: 99%
“…To date, this complementary technique has been used in the evaluation of common and also infrequent ophthalmologic diseases such as diabetic retinopathy [25][26][27][28][29][30][31][32][33][34][35]; congenital and acquired retinopathies [36]; preretinal, intraretinal, and subretinal neovascularization [37][38][39][40][41][42][43][44][45][46][47]; retinal venous occlusions [48][49][50][51]; retinal artery occlusions [52]; macular teleangiectasia [53][54][55][56][57]; senile macular degenerations [58][59][60]; glaucoma [60][61][62][63][64][65][66][67]; uveitis [68][69][70][71]; and optic neuropathies…”
Section: Introductionmentioning
confidence: 99%